A comparative analysis of the different HIV testing techniques used in Zambia: data from a clinical performance study - Loveness Mukuka; Andros Theo; Precious Simushi; Mowa Zambwe; Peter J. Chipimo (BMC Research Notes)
Abstract Background Approximately 40 million people globally are living with HIV (PLWH) and more than 50% of these PLWH reside in Eastern and Southern Africa. Zambia has an adult HIV-1 prevalence (ages 15–49) of 11.1 [10.5–11.6] %, among the highest in the world (UNAIDS, 2021). In 2020, 1.5 million people were estimated living with HIV-1 in Zambia. Despite the success of many HIV preventative strategies, and worldwide sensitization to know one’s status, there remains a substantial number of people with HIV who are unaware of their infection and are still infecting others. Globally, about 20% of HIV infections are due to transmissions from recently infected individuals. As Zambia’s adult HIV prevalence is about 11.1%, if 3rd generation RDTs are used for first time HIV testing, all the people tested that are within the acute period will be given a false negative result. Hence the need to develop better first line HIV testing techniques. Method A quantitative descriptive approach was used to analyze samples of 2564 participants, between the ages of 15 to 95 years from two Lusaka sites. The 2564 participants were subjected to OraQuick ADVANCE Rapid HIV-1/2 Antibody Test and Abbot Determine™ HIV-1/2 antibody test, if Reactive on either test, the result was confirmed on Uni-Gold™ Recombigen® HIV-1/2 rapid test as a confirmatory RDT. An EDTA tube of blood for each of the 2564 participants was collected and sent to the central laboratory for further testing on fourth generation Abbot ARCHITECT HIV Ag/Ab Combo and then any discrepancies were confirmed on Genscreen™ ULTRA HIV Ag-Ab. Using a systematic analysis technique, quantitative methods were applied to evaluate different variables and compare them against each other to find relationships. The data were cleaned using Microsoft excel and were analyzed using SPSS version 25.0. Results The Abbot ARCHITECT HIV Ag/Ab Combo fourth generation assay was used as the gold standard, of the total 2564 tested 267 (10.4%) were reactive tests and 2297(89.6%) non-reactive. OraQuick ADVANCE Rapid HIV-1/2 test detected 245(9.6%) reactive tests and 2319 (90.4%) non-reactive, Abbot Determine™ HIV-1/2 test detected 249(9.7%) true reactive tests and 2315 (90.3%) non-reactive, all reactive tests on the first two RDTs were confirmed on Uni-Gold™ Recombigen® HIV-1/2 rapid test which detected 247 (9.6%) reactive and 2317 (90.4%) non-reactive. These results show that compared to the gold standard the 3 RDTs missed more than 18 (6.7% of the total 267) reactive results. This means that in every 15 tests done, 1 result is a false negative. Conclusion Third generation RDTs were unable to detect a good number of acute positive cases and are therefore unreliable. There is therefore need for the use 4th generation Rapid test to capture the positive cases currently being missed out.